A randomized controlled trial of the effect of a psychoeducational intervention program on quality of life of patients with gynecological cancers - Eman Ahmed Fawzy Darwish; Salwa Elsayed Abdelhalim Tayel; Mahmoud Elsayed Hanafi Meleis; Heba Essam Abou Elwafa; Fadia Samir Shaaban Marouf (Alexandria Journal of Medicine)
Background Women diagnosed with gynecological cancer often suffer from physical, psychological, and social challenges as well as sexuality-related concerns and hence poor life quality. This study attempted to evaluate the effect of psychoeducational intervention program on quality of life among patients with gynecological cancers.Methods A randomized controlled trial design was used where the eligible gynecological cancer women (n = 100) were allocated randomly into the intervention group receiving a four‐session, 8‐week-long psychoeducational program (n = 50) or the control group receiving routine care (n = 50). Allocation concealment was used to avoid selection bias. A structured interview questionnaire was used at baseline assessment to obtain data regarding the socio-demographics as well as clinical traits of studied women. Additionally, data on quality of life at baseline and after implementation of the program were collected using the Arabic version of Functional Assessment of Cancer Therapy-General version 4 (FACT-G).Results The study revealed that gynecological cancer women receiving psychoeducational intervention program experienced a significantly greater improvement in their total life quality in addition to significant improvements across different domains as measured by FACT-G.Conclusion The psychoeducational intervention program contributed positively in improving the life quality among patients with gynecological cancers.